Histologic Variants of Kaposi Sarcoma in the Gastrointestinal Tract: A Contemporary Multi-institutional Clinicopathologic Analysis of 46 Cases. (17th November 2022) - Zheng, Wei; Obeng, Rebecca C.; Graham, Rondell P.; Lui, Shu; Cheng, Jerome; Alexiev, Borislav A.; Quigley, Brian; Krasinskas, Alyssa; Yang, Guang-Yu; Escobar, David; Liu, Xiuli; Navale, Pooja; et al.
Abstract : Kaposi sarcoma (KS) can pose diagnostic challenges in biopsy specimens. Multiple histologic variants of cutaneous KS have been described; however, the histomorphologic spectrum of gastrointestinal (GI) KS has not been systematically studied. This large series comprehensively evaluated 46 cases of KS involving the GI tract and identified 7 histomorphologic variants, some that have not been previously described. Five of them are inconspicuous but have unique morphologic patterns, including lymphangioma/lymphangiectatic–like (n=17), mucosal hemorrhage/telangiectatic–like (n=17), mucosal inflammation–like (n=15), granulation tissue–like (n=13), and mucosal prolapse–like (n=4) variants. These variants can be easily misdiagnosed or misinterpreted on routine examination if KS is not considered, and if the immunohistochemical stain for human herpesvirus-8 is not performed. The other 2 morphologic variants present as spindle cell proliferations and are the GI stromal tumor–like (n=8) and inflammatory myofibroblastic tumor–like (n=2). These variants raise a broad differential diagnosis of spindle cell tumors of the GI tract and could pose diagnostic challenges. In summary, GI KS lesions exhibit variable, often unconventional histomorphologic patterns. KS should be included in the differential diagnosis even if features of conventional KS are not seen, particularly in limited biopsies in immunocompromised patients, such as those with human immunodeficiency virus infection. Although the clinical significance of these morphologic variants is yet to be determined, they are nonetheless important from a diagnostic standpoint. Misdiagnosis and delay in appropriate management can be avoided by recognizing the morphologic diversity of GI KS and appropriately utilizing the human herpesvirus-8 immunohistochemical stain.